The petroleum engineering handbook sustainable operations - Khan, M. Ibrahim (Gulf Pub., 2007)
This is the first book in the petroleum sector to shed light on the real obstacles to sustainable development and provides solutions to each problem encountered. Each solution is complete with an economic analysis that clarifies why petroleum operations can continue with even greater profit than before while ensuring that the negative environmental impact is diminished. The new screening tools and models proposed in this book will provide one with proper guidelines to achieve true sustainability in both technology development and management of the petroleum sector.
Statement of responsibility from cover.
Keywords: Petroleum engineering -- Handbooks, manuals, etc.; elektronické knihy; electronic books